MODAL BUDAYA DAN MODAL SOSIAL: PENUNJANG BERKEMBANGNYA TOKO BANGUNAN YUNA JAYA - Ayu Musliha (LPPM UNISDA, 2021)
: In fact, the development of a business does not only talk about how economic capital is managed by business actors. Cultural capital and social capital are also important aspects in the process of developing a business. This research uses qualitative methods with data collection techniques through interviews and participatory observation. The informant investigates the business owner and one of the customers. The results of the study indicate that the capital owned by the business owner benefits the business actor for running his business. Meanwhile, social capital in the form of trust can enhance existing social networks and build new social networks. The maintenance process is carried out by business owners through loyalty to sales / bosses and buyers. So, it can be concluded that social capital and cultural capital also play an important role in the process of developing a business.